Spectral collocation method for transient thermal analysis of coupled conductive, convective and radiative heat transfer in the moving plate with temperature dependent properties and heat generation. (November 2017) - Ma, Jing; Sun, Yasong; Li, Benwen
Graphical abstract: (a) Physical model and (b) temperature distribution of transient heat transfer in the moving plate. Highlights: Transient heat transfer in the moving plate is analyzed. SCM has high accuracy and exponential convergence rate for the present problem. Heat generation and thermal properties are considered as functions of temperature. Effects of dimensionless parameters on transient temperature are investigated. Abstract: The spectral collocation method is developed and formulated to solve transient thermal process in the moving plate with temperature dependent properties and heat generation. In this moving plate, thermal conductivity and surface emissivity are assumed as linear functions of temperature; and heat transfer coefficient and heat generation are considered as power exponent functions of temperature. The time domain of energy equation is discretized by fully implicit Euler scheme; the spatial domain of energy equation is discretized by Chebyshev polynomials and Chebyshev collocation points. Numerical results by the spectral collocation method are compared with analytical solutions. This comparison indicates that the spectral collocation method can obtain very high accuracy even using few nodes. Meanwhile, the spectral collocation method can provide the exponential node convergence rate for this present problem. Moreover, the effects of various dimensionless parameters, such as Peclet number, heat generation parameters, thermal conductivity coefficient, surface emissivity coefficient, power exponent of heat transfer coefficient, convective-conductive parameter, radiative-conductive parameter and dimensionless ambient temperature on transient temperature, efficiency and effectiveness of the moving plate are comprehensively investigated.